Analisis Anak Berkebutuhan Khusus Tunagrahita dengan Kesulitan Menulis pada Siswa Kelas 3 di Sekolah Dasar Negeri Pasar Baru 1 - Nurfadhillah, Septy; Octaviana, Putri; Utami, Dini (Lembaga Yasin AlSys, 2022)
This study aims to describe the difficulties in learning to write for children with special needs with mental retardation and identify the causes of difficulties in learning to write in grade 3 students at SD Negeri Pasar Baru 1. This study uses descriptive qualitative research methods, with observation, interview, observation and documentation techniques. Based on the results of the study, some of the writing difficulties experienced by students with special needs did not recognize the letters of the alphabet as a whole, their writing skills had not yet developed, and students were still rigid in using stationery. this condition is influenced by the students' visual motor coordination which is not yet adequate. For this reason, researchers are interested in examining writing difficulties in children with special needs for mental retardation.